Comparison of two alcohol hand rubbing techniques regarding hand surface coverage among hospital workers: a quasi-randomized controlled trial - Yumi Suzuki; Motoko Morino; Ichizo Morita; Sumie Ohiro (Antimicrobial Resistance and Infection Control, 2022)
Abstract Background The adapted 6-step without interlock (A6Sw/oI) hand rub technique, commonly practiced in Japan, adds the “wrist” but omits the “interlock” step compared to the WHO 6-step technique (WHO6S). The first objective of this study was to assess the differences of the two techniques regarding surface coverage. The second objective was to analyze the coverage differences between hand sizes. Methods Hospital workers went under stratified quasi-randomization by glove size. The overall mean coverage, and the coverage of the sections of the hands were evaluated by fluorescent dye-based coverage assessment using a digital device with artificial intelligence technology. Results Total of 427 workers were randomly allocated to WHO6S (N = 215) or the A6Sw/oI (N = 212). The overall mean dorsum coverage by WHO6S and A6Sw/oI was 90.6% versus 88.4% (p < 0.01), and the percentage of the participants with insufficient coverage of the backs of the four fingers ranged from 0.0–7.4% versus 28.2–51.4% (p < 0.001). Dorsum coverage varied largely between hand size for both techniques, and significant differences were found between small and large hands. Conclusion The WHO6S was superior to the locally adapted technique regarding hand surface coverage. Hand size should be considered when assessing coverage differences between procedures. No trial registrations or fundings.